Combined LC-MS-based metabolomics and GC-IMS analysis reveal changes in chemical components and aroma components of Jujube leaf tea during processing - Jiang, Nan; Hou, Shujuan; Liu, Yuye; Ren, Peixing; Xie, Nuoyu; Yuan, Ye; Hao, Qing; Liu, Mengjun; Zhao, Zhihui (Frontiers in Plant Science, 2023)
Making tea from jujube leaves changed the chemical composition and aroma composition of jujube leaves. Here, Through LC-MS, GC-IMS, and GC-MS technology, we have revealed the effect of jujube leaf processing changes on metabolites. LC-MS identified 468 non-volatile metabolites, while GC-IMS and GC-MS detected 52 and 24 volatile metabolites, respectively. 109 non-volatile metabolites exhibiting more pronounced differences were screened. Most lipids and lipid-like molecules, organic acids, amino acids, and flavonoids increased significantly after processing. GC-IMS and GC-MS analysis revealed that the contents of aldehydes and ketones were significantly increased, while esters and partial alcohols were decreased after processing into jujube leaf tea. The main flavor substances of fresh jujube leaf and jujube leaf tea were eugenol and (E) - 2-Hexenal, respectively. Furthermore, amino acids and lipids were closely linked to the formation of volatile metabolites. Our study provided new insights into the changes in metabolites of jujube leaves processed into jujube leaf tea, and had great potential for industrial application. It laid a foundation for further research on fruit tree leaf tea.